2006
DOI: 10.1002/jemt.20309
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural characteristics of human granulosa cells in a coculture system for in vitro fertilization

Abstract: The use of somatic cells for cocultures during in vitro fertilization (IVF) is currently finalized to obtain a higher number of healthy and viable embryos with a high potential of implantation. Among the different cell lines that can be used as feeder cells for cocultures, granulosa cells (GCs) are autologous cells, safe and easy to recover. The aim of the present study was to analyze the fine structure of human GCs used in a coculture system to evaluate, from a morphodynamic point of view, their role in suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 50 publications
2
29
1
1
Order By: Relevance
“…Annular junctions arise from phagocytised gap junctions as described for granulosa cells from human preovulatory follicles. 37,38 We here interpret the frequent observation of annular junctions in context with the increased follicular atresia.…”
Section: Discussionsupporting
confidence: 59%
“…Annular junctions arise from phagocytised gap junctions as described for granulosa cells from human preovulatory follicles. 37,38 We here interpret the frequent observation of annular junctions in context with the increased follicular atresia.…”
Section: Discussionsupporting
confidence: 59%
“…Other authors have similarly shown granulosa cells with abundant RER (Nottola et al, 2006) and have considered them as G-rich protein-synthetic cells. However, it has also been demonstrated that, in cell culture, the numerous polyribosomes and, in some circumstances, a disaggregation of polyribosomes are connected to a marked depression of protein synthesis during mitosis (Ghadially, 1988).…”
Section: T 3 and Cov434 Survivalmentioning
confidence: 84%
“…In nearly all studies on buffalo IVEP, presumptive zygotes are subject to an in vitro culture (IVC) system, involving use of TCM-199, a complex medium coculture with buffalo oviductal epithelial cells or granulosa cells and supplemented with serum, even though it has been demonstrated that primary oviduct (Mugnie et al 2009) and granulosa cell (Nottola et al 2006) cultures secrete a series of factors that act in a paracrine manner stimulating development to the blastocyst stage. This system is complex and associated blastocyst yield is very low.…”
Section: Introductionmentioning
confidence: 99%